A clinical and biochemical laboratory profile to measure the severity of dengue fever and their outcome - Sushma, Maddipatla; Nagabhushana, M. V.; Reddy, M. Dharaneedhar (International Journal of Advances in Medicine, 2020)
Background: To identify various manifestations of dengue fever, complications, and to measure their association with laboratory findings. Methods: 100 cases of suspected adults between 20-70 years of age with clinical features suggestive of dengue infection and patients presenting with fever of acute onset (<2 weeks), pain abdomen, vomiting, rash, flushed appearance and bleeding manifestation were studied. All cases were followed up for the clinical and laboratory parameters and treated according to WHO guidelines. Results: 36 were classified as classical dengue fever, 33 as dengue haemorrhagic fever (DHF), 15 as dengue shock syndrome (DSS), and 16 as dengue-like illness (DLI) and the common age group was 30-40 year (50%). Most (66%) of the patients were male. The common presenting symptoms was fever 65%, vomiting (40%), abdominal pain (40%), myalgia (7%), etc. Hepatomegaly (53%), ascites (1%), splenomegaly (8%) was noted. The mean platelet in the present study was 41870 cells/cu mm. Elevated liver enzymes and elevated serum creatinine was found in complicated forms of disease. The prothrombin time ranged from 11-60 sec with a mean of 19.5 sec. Conclusions: The treatment of dengue is mainly supportive, but early institution and meticulous monitoring are the important steps for positive outcome. Much more awareness, vigilance and research in the diagnostic modalities are further needed to avoid unnecessary panic and platelet transfusions.